2009
DOI: 10.1097/mph.0b013e3181a1c0e8
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Flow Cytometry Data Analysis for Evaluation of Minimal Residual Disease in Bone Marrow From Acute Leukemia Patients During Treatment

Abstract: Low levels of leukemia cells in the bone marrow, minimal residual disease (MRD), are considered to be a powerful indicator of treatment response in acute lymphatic leukemia (ALL). A Nordic quality assurance program, aimed on standardization of the flow cytometry MRD analysis, has been established before implementation of MRD at cutoff level 10 as one of stratifying parameters in next Nordic Society of Pediatric Hematology and Oncology (NOPHO) treatment program for ALL. In 4 quality control (QC) rounds 15 labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
2
24
0
2
Order By: Relevance
“…Modulation of several markers is another confounding variable important for MRD analysis as we have seen in some of our discordant cases and as was reported before (30). Interestingly, similar to the NOPHO group (29) we observed that the concordance was higher in precursor B when compared with T-cell ALL.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Modulation of several markers is another confounding variable important for MRD analysis as we have seen in some of our discordant cases and as was reported before (30). Interestingly, similar to the NOPHO group (29) we observed that the concordance was higher in precursor B when compared with T-cell ALL.…”
Section: Discussionsupporting
confidence: 82%
“…Per time point best qualitative agreement was in exchanged LMD from D-15 (86%) as opposed to those from D-33 (52%). Also in the NOPHO QC study (29) at a cutoff level 10, laboratories obtained a high concordance (91.6%). Remarkably, in our study, with no prior standardization and utilizing two very different FCM-MRD methodologies, qualitative agreement was 80% for D-33 and quantitative agreement of D-15 samples was 80.8%.…”
Section: Discussionmentioning
confidence: 85%
“…Despite differences in cytometers and software usage, blinded inter-laboratory tests of list-mode data interpretation gave highly concordant results (intraclass correla- robustness of this approach in refining MRD-based stratification with measurements on day 15 (37). The feasibility of standardized multicentric MRD assessment has also been shown by others groups (66,67). Six-eightcolor-FCM MRD techniques are currently employed for leukemia immunophenotyping.…”
Section: Standardization Of Flow Cytometric Methods Formentioning
confidence: 90%
“…Существен-ными недостатками мониторинга МОБ методом про-точной цитометрии по сравнению с количественной полимеразной цепной реакцией (ПЦР) являются субъективность и сложность стандартизации в рамках многоцентровых исследований [8,14]. В то время как технология молекулярно-генетического ис следования МОБ хорошо отработана и стандартизована [8,14,15], опубликовано лишь несколько работ по начальным этапам стандартизации цитометрического мониторин-га ОЛЛ в рамках отдельных исследовательских групп [16][17][18].…”
Section: фундаментальные исследования в практической медицине на соврunclassified
“…Однако сложности применения данного варианта ПЦР определяют необходимость разработ-ки стандартизованных протоколов определения МОБ проточной цитометрией в рамках различных терапев-тических протоколов. На данный момент такие по-пытки проводятся группами AIEOP-BFM [16], UKALL [17], NOPHO [18]. Кроме того, высокий уровень стан-дартизации определения МОБ при ОЛЛ предлагает не связанная с определенными терапевтическими протоколами группа EuroFlow [14].…”
Section: рис 3 пример последовательного выделения опухолевых клетокunclassified